In the footsteps of chronic childhood malnutrition: an endemic global health problem in Chota, Cajamarca - Peru - Oblitas Gonzales, Aníbal (2020)
The present study aims to analyze chronic child malnutrition as a social fact, an expression of underdevelopment and a consequence of social inequalities (conventional epidemiology versus critical epidemiology) that are generated in the spaces of daily life of the most unprotected. Its approach implies departing from conventional epidemiology - from its "cold" statistical determinants and its "famous" multicausality (cause / effect) - where the individual and biologist level prevails over the community and social level. Furthermore, it is known that this has brought with it fragmentation and stagnation in its approach; since, no matter how “exact” and “exhaustive” their “methods” are, at the moment the results of their interventions are insufficient. In this context we propose an intervention from the critical epidemiology of: Breilh J (2003), Bengoa JM (2008), Lévi-Strauss (1956), Arendt Hannah (1997), accepting that this is a complex reality (social fact) that has dimensions (general, particular and singular), and where each individual becomes a unique and unitary whole. For this, it is a priority to establish health policies with a humanized care character (connectivity, receptivity and reciprocity), and the strengthening of the participation of the empowered state and organized civil society. In conclusion: extirpating chronic malnutrition from the entrails of socially excluded and vulnerable populations will be easier, if we look at it as a social fact, rather than simple "statistics", if we prioritize the collective over the individual, and if we count on an empowered population with the optimism to fertilize their social well-being.